Characteristics of multi-channel reservoir computing based on mutually-coupled spin-VCSELs: a comprehensive investigation - Jiang, Li; Deng, Sha-Sha; Song, Wei-Jie; Zou, Mei-Ling; Jia, Xin-Hong; Tang, Yu-Quan; Bao, Ming-Yu; Lv, Jiang-Tao (Applied physics. B, Lasers and optics, 2024)
We studied the characteristics of a four-channel multi-task reservoir computing (RC) system based on mutually-coupled and optically pumped spin vertical-cavity surface-emitting lasers (Spin-VCSELs). By analyzing bifurcation and state diagrams, we investigated the polarization dynamics of the system. Additionally, we examined the effects of key parameters such as coupling strength, injection strength, frequency detuning, optical pumping intensity, and pump polarization ellipticity on RC performance, with one-step time-series prediction as the benchmark. Our findings indicate that an increase in coupling strength results in a reduced frequency detuning range, accompanied by a lower normalized mean squared error (NMSE). Excessive coupling strength and optical pumping intensity are detrimental to RC performance. The influence of pump polarization ellipticity is smaller and exhibits a symmetry feature. Furthermore, the parameter optimization regime for orthogonal polarized optical coupling (OPOC) is wider than that for parallel polarized optical coupling (PPOC). Under optimized parameters, both PPOC and OPOC-based RC system can achieve NMSE as low as 0.033 and 0.041 respectively. This work can provide a valuable insight on the design and mechanism analysis for parallel and multi-task processing RC systems based on the platform of Spin-VCSELs.